2017
DOI: 10.1002/cncr.30680
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and feasibility of sorafenib as a maintenance agent after allogeneic hematopoietic stem cell transplantation for Fms‐like tyrosine kinase 3‐mutated acute myeloid leukemia

Abstract: Sorafenib treatment after HSCT appears to be feasible and highly effective with dose individualization according to patient tolerability. Further analysis is needed to evaluate the immunomodulating role of sorafenib after HSCT. The data from the current support prospective controlled trials of sorafenib after HSCT. Cancer 2017;123:2867-74. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 28 publications
2
67
0
Order By: Relevance
“…A growing body of clinical evidence indicates that whether sorafenib is used before or after transplantation, sorafenib in combination with allo-HSCT might benefit patients with FLT3-ITD AML. [10][11][12][13][14] However, these studies had small samples, and to our knowledge, there is a lack of comparative studies on the efficacy of sorafenib therapy before and after transplantation. In this large-sample, retrospective study, we compared the effects of sorafenib at different time points on the outcomes of patients with FLT3-ITD AML undergoing allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of clinical evidence indicates that whether sorafenib is used before or after transplantation, sorafenib in combination with allo-HSCT might benefit patients with FLT3-ITD AML. [10][11][12][13][14] However, these studies had small samples, and to our knowledge, there is a lack of comparative studies on the efficacy of sorafenib therapy before and after transplantation. In this large-sample, retrospective study, we compared the effects of sorafenib at different time points on the outcomes of patients with FLT3-ITD AML undergoing allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…8 A growing body of clinical studies suggests that chemotherapy combined with sorafenib might promote longer remissions for patients with FLT3-ITD AML, especially for patients younger than 60 years. [12][13][14] In this study, we retrospectively evaluated the effect of sorafenib therapy on the outcomes of patients with FLT3-ITD AML undergoing allo-HSCT. [12][13][14] In this study, we retrospectively evaluated the effect of sorafenib therapy on the outcomes of patients with FLT3-ITD AML undergoing allo-HSCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the RI post ASCT, including late relapses, has been shown to be higher than following allo‐HSCT, due to the absence of a graft‐vs‐leukemia effect . In patients allotransplanted, several attempts at reducing the RI post‐transplant have given interesting results, using tyrosine kinase inhibitors such as sorafenib, midostaurin, or PD1/PD1L inhibitors. No such approach has been tested so far in the context of ASCT although the rationale would be solid.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of NRM or cGVHD were no different between groups. Meanwhile, other retrospective studies have also reported encouraging outcomes with the use of sorafenib as post-alloHCT maintenance therapy [56,57].…”
Section: Gilteritinibmentioning
confidence: 99%